PARADOKSALITAS PEMOSISIAN PEREMPUAN NOVEL COLOMBA KARYA PROSPER MERIMEE - Wening Udasmoro (Jurnal Kawistara, 2015)
Women have been narrated by men authors since classical literature; this has continued into contemporary literature. In the 19th century, many authors were interested in narrating and positioning women in their novels. This period can be considered one of transition, in which traditionality and modernity were contested because of influences from the industrial revolution and many other social movements in Europe. This period was also one of challenge, with the appearance of Gustave Flaubert’s novel Madame Bovary, which was questioned because of moralistic issues. If in the early 19th century traditionality was represented by Eugénie Grandet and Balzac’s figures of woman, but in the middle of the century Flaubert dealt with freedom of sexuality, what discourses were presented in between these two different periods? This article aims at explaining the bridging of the gap between the symbols of traditionality and modernity, especially through the representation of women. Mérimée’s novel, Colomba, depicts the agency of a woman named Colomba. In this novel, Mérimée not only showed the position of women vis à vis men in parental or conjugal relation, like in the novels Eugénie Grandet or Madame Bovary. Rather, the author attempted to look at the relationship between masculinities and femininities in a Corsican context, in which the intersection of gender and social class (as well as traditions) was different than in the Parisian context. The relation between the novel and the social structure in the 19th century Europe plays an important part in the discussion and explanation of the relationship between the literature and social narration of that period